AB0760 Advanced oxidation protein products in serum of patients with systemic sclerosis: a possible indicator of clinical evolution. (12th June 2018) - Sighinolfi, G.; Colaci, M.; Spinella, A.; Lumetti, F.; Artoni, E.; Salvarani, C.; Giuggioli, D.
Abstract : Background: Systemic sclerosis (SSc) is a chronic, multisystem connective tissue disease characterised by by immune dys-regulation, obliterative microvasculopathy and fibrosis. Endothelial dysfunction, immune system imbalance and fibroblast activation constitute the three major factors of the pathogenetic process. In this context, oxidative stress could play a significant role through direct damage of endothelial cells and the persistent activation of the immune system. 1, 2 Objectives: This study investigated the presence of advanced protein oxidation products (AOPP) in serum of patients with SSc and its correlation with disease's features. Methods: 50 patients with SSc (M:F 1:7, mean age 57.3±11.2 SD, mean duration of disease 10±9.1 SD years), were screened for AOPP in the serum, using the AOPP OxiSelect Kit of CELL BIOLABS (San Diego, Ca, USA). Among 50 SSc patients, 39 had limited cutaneous subset, while 11 had the diffuse one. Anamnestic and clinical data were collected for all SSc patients. As a control group 50 consecutive healthy subjects, sex and age matched, were recruited. Results: We found serum levels of AOPP increased in the SSc group compared with the controls (p<0.0001) with mean values of 336.9±167.8 mmol/L and 167.5±59.2 mmol/L, respectively. In addition, higher levels of AOPP directly correlated with the diffuse cutaneous subset (p=0.0242), presence of digital ulcers (p=0.005), esophagopathy (p=0.006) and pulmonary fibrosis (p=0.0128). Conclusions: Serum AOPP levels are significantly higher in patients with SSc than in controls. In addition, the correlations of AOPP with SSc diffuse cutaneous subset, digital ulcers, and pulmonary involvement (indicative of progressive disease and worse prognosis) suggest a possible role of this marker in the identification of the cases with worse clinical evolution. The data of this preliminary study should be confirmed on larger case series and analysed in prospective studies, in order to understand its eventual usefulness during the follow-up of SSc patients. References: [1] Ferri C, Valentini G, Cozzi F, Sebastiani M, Michelassi C, La Montagna G, et al. Systemic Sclerosis: Demographic, Clinical, and Serologic Features and Survival in 1, 012 Italian Patients. Medicine (Baltimore). 2002; 81:139–153 [2] Steen VD. The many faces of scleroderma. Rheum Dis Clin North Am. 2008; 34:1–15 Disclosure of Interest: None declared